The division of swimming strokes into phases, based upon kinematic parameters - Wiegand, K.; Wuensch, D.; Jaehnig, W. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
Physical educators, coaches, and athletes should have objective criteria for the determination of the development of swimming strokes, i.e., hose factors and basic parameters that establish the structural fundamentals of top class performances. One of the main prerequisites for accomplishing this is, among others, the quantitative assessment of swimming strokes to make them comparable with each other. It will be possible to determine the essentials of swimming strokes only by analyzing them quantitatively. Such an approach will lead to an understanding of the laws of swimming techniques including their hydromechanical aspects. The authors believe that the distribution of swimming strokes into phases based upon objective criteria is of major importance.